2014
DOI: 10.1007/s10555-013-9481-1
|View full text |Cite
|
Sign up to set email alerts
|

Src signaling pathways in prostate cancer

Abstract: Knowledge of the molecular events that contribute to prostate cancer progression has created opportunities to develop novel therapy strategies. It is now well established that c-Src, a non-receptor tyrosine kinase, regulates a complex signaling network that drives the development of castrate-resistance and bone metastases, events that signal the lethal phenotype of advanced disease. Preclinical studies have established a role for c-Src and Src Family Kinases (SFKs) in proliferation, angiogenesis, invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 115 publications
(116 reference statements)
1
87
0
1
Order By: Relevance
“…Consequently, further options are needed as alternatives to docetaxel. It has been reported that overexpression of a nonreceptor tyrosine kinase, Src, during the transition from an androgen-dependent to an androgen-independent state in prostate cancer contributes to a poorer prognosis and reduced overall survival (3). Src is an integrator of divergent signals, facilitating the action of other oncogenic signal proteins, making it an attractive target for the treatment of several human tumors (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, further options are needed as alternatives to docetaxel. It has been reported that overexpression of a nonreceptor tyrosine kinase, Src, during the transition from an androgen-dependent to an androgen-independent state in prostate cancer contributes to a poorer prognosis and reduced overall survival (3). Src is an integrator of divergent signals, facilitating the action of other oncogenic signal proteins, making it an attractive target for the treatment of several human tumors (3).…”
mentioning
confidence: 99%
“…It has been reported that overexpression of a nonreceptor tyrosine kinase, Src, during the transition from an androgen-dependent to an androgen-independent state in prostate cancer contributes to a poorer prognosis and reduced overall survival (3). Src is an integrator of divergent signals, facilitating the action of other oncogenic signal proteins, making it an attractive target for the treatment of several human tumors (3). In addition, in prostate cancer, androgen-independent prostate cancer cells develop the ability to survive and thrive by stimulating oncogenic pathways that Src regulates (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic domain possesses the intrinsic tyrosine kinase activity of the molecule and is followed by a C-terminal regulatory domain [16]. The intricacy regulations of the activity of the SFKs have been summarized before [9,10,17].…”
Section: The Molecular Basis Of Src Signaling Regulationmentioning
confidence: 99%
“…Recently, the Src signaling pathways in prostate cancer had been reviewed by Varkaris et al [10] Illuminating the underlying mechanisms of SRC signaling in HCCs is required for improving diagnosis, therapy and prognosis. In this study, we reviewed newly found regulation pathway of SRC signaling, and novel molecules that directly or indirectly targeted Src signaling which can be utilized in the treatment of liver cancer.…”
Section: Introductionmentioning
confidence: 99%